Study of Bacteriological pathogen causing neonatal sepsis at NICU in Ad-din medical college hospital (Northern International Medical College Journal, 2015)
Objective : To determine the common causative bacterial agents of neonatal sepsis and their antimicrobial susceptibility in NICUMethods : Newborns with clinical signs of septicemia and positive blood culture during twelve months were prospectively studied. Samples for blood cultures, complete blood count, C-reactive protein, sugar, electrolytes were obtained ; ampicillin and gentamycin were started empirically.Result : Seven hundred and three neonates were investigated to rule out of sepsis. The male, female ratio was 1.3:1 and 56(63.63%) of patients were preterm and 32(36.36%) were term neonates. There were 68 (77.27%) cases of Early onset neonatal sepsis (EONS) and 20(22.64%) of Late onset neonatal sepsis (LONS). Coagulase negative staphylococcus (CONS) was the most common 37(42.04%) Gm+ve pathogen causing early onset neonatal sepsis and Acinetobacter was common Gm-ve pathogen in both early onset 16(18%) and late-onset 8 (9%) sepsis. CONS sepsis showed high degree of resistance to commonly used antibiotics; ampicillin (86.5%), oxacillin (60%),cefotaxime (67%) but comparatively low resistance to vancomycin (0%), gentamicin (25%), Levofloxacin(36%) & Imipenem (49%). Acinetobacter were highly resistant to ampicillin (100), gentamicin(75%), cefotaxime(100) and sensitive to Amikacin (58.33%), ciprofloxacin (54.16%), Levofloxacin and Imipenem (62.5%)and Colistin (95.83%).Conclusion : Neonatal sepsis in our NICU is mainly caused by grampositive organisms, which are developing resistance to commonly used antibiotics. The initial empirical choice of Ampicillin and Gentamicin appears to be unreasonable for our environment.Northern International Medical College Journal Vol.5(1) 2013: 297-300